2009
DOI: 10.1038/emboj.2009.203
|View full text |Cite
|
Sign up to set email alerts
|

Distinct donor and acceptor specificities of Trypanosoma brucei oligosaccharyltransferases

Abstract: Asparagine‐linked glycosylation is catalysed by oligosaccharyltransferase (OTase). In Trypanosoma brucei OTase activity is catalysed by single‐subunit enzymes encoded by three paralogous genes of which TbSTT3B and TbSTT3C can complement a yeast Δstt3 mutant. The two enzymes have overlapping but distinct peptide acceptor specificities, with TbSTT3C displaying an enhanced ability to glycosylate sites flanked by acidic residues. TbSTT3A and TbSTT3B, but not TbSTT3C, are transcribed in the bloodstream and procycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
174
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(187 citation statements)
references
References 49 publications
13
174
0
Order By: Relevance
“…4,12 The various enzymes from a single organism can have different glycan and protein substrate specificities, such that gene duplication and divergence may have increased the catalytic range of efficient glycosylation. [13][14][15][16][17] Higher eukaryotes have evolved multiprotein complex OTases, in which subunits are involved in selection of mature glycan substrate and regulation of activity. [18][19][20] Duplication and divergence of multiprotein OTase subunits has also occurred, with genes encoding Stt3p and Ost3/6p proteins present in two copies in some organisms.…”
Section: Introductionmentioning
confidence: 99%
“…4,12 The various enzymes from a single organism can have different glycan and protein substrate specificities, such that gene duplication and divergence may have increased the catalytic range of efficient glycosylation. [13][14][15][16][17] Higher eukaryotes have evolved multiprotein complex OTases, in which subunits are involved in selection of mature glycan substrate and regulation of activity. [18][19][20] Duplication and divergence of multiprotein OTase subunits has also occurred, with genes encoding Stt3p and Ost3/6p proteins present in two copies in some organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bushkin et al (14) presented new evidence demonstrating the existence of functional N-glycosyla-tion in the intraerythrocytic stages of P. falciparum. In general, protozoan parasite N-glycosylation patterns are atypical of those described in higher eukaryotes (15,16). In P. falciparum, the secondary loss of enzymes related to the biosynthesis of N-glycosylation precursors and the quality control of glycoprotein folding in the endoplasmic reticulum (17,18) result in a very unusual N-glycosylation (14) that, if essential, could be therapeutically exploitable.…”
mentioning
confidence: 99%
“…Furthermore, it was observed that POTs can transfer the glycan to other glycosylation sites than the one glycosylated by the endogenous OST complex. TbSTT3B and TbSTT3C when replacing yeast STT3, did have different activities towards some of the glycosylation sites, furthermore, sites which are normally not occupied were glycosylated by T. brucei STT3B and STT3C [21]. TbSTT3A was highly selective for acidic peptide acceptor sites, TbSTT3B has a broad specificity for the acceptor sites, whereas TbSTT3C preferentially glycosylated acidic peptide acceptors.…”
Section: Improving N-glycosylation Efficiency Using Protozoan Oligosamentioning
confidence: 95%
“…The organisms cope with this variation in the LLO structures, by expressing a distinct set of STT3 paralogous. T. brucei possess three STT3 paralogoues, TbSST3A being specific for Man5GlcNAc2, TbSTT3B being specific for Man9GlcNAc2 [21].…”
Section: Improving N-glycosylation Efficiency Using Protozoan Oligosamentioning
confidence: 99%